Enhancing Financial Reporting Quality Through Good Governance and Fiscal Capacity: Evidence from West Java - Ibnu Nizam Al-Maraghi; Ywang Smaradewane Ratunemas Nagari (Politeknik Ganesha Medan, 2026)
The quality of local government financial statements is a critical indicator of public accountability and the reliability of information for decision-making. This study examines the factors influencing the issuance of unqualified audit opinions on local government financial statements in West Java Province for the period 2019–2023. Using a binary logistic regression model with random effects on panel data from 27 regencies/cities for five years (135 observations), this study examines the effects of budget capacity, bureaucratic reform, audit recommendation follow-up, and public information disclosure on audit opinions. The estimation results show that budget capacity and public information disclosure have a significantly negative relationship with unqualified opinions, while bureaucratic reform has a significantly positive effect. The follow-up of audit recommendations is not statistically significant. These findings imply that strategies to improve audit opinion quality should prioritize bureaucratic reform and institutional governance strengthening. Fiscal capacity and information transparency must be strategically managed to anticipate excessive audit complexity. This study provides empirical evidence that governance quality, rather than financial resources, plays a more decisive role in determining the quality of local government financial reporting.